(untitled) (Ustozlar uchun, 2025)
Nowadays a number of regulatory and legal documents are being developed on auditing and giving conclusions financial statements of economic entities of various ownership types operating in the territory of the Republic of Uzbekistan based on the requirements of international audit standards. In this article explained the theoretical and practical considerations of the use of international audit standards by auditors in conducting risk-based audits of business entities. In addition, suggestions and recommendations were developed to eliminate inconsistencies in financial statements and reduce the risk of significant misstatements.